Multi-Task Scheduling Optimization Method Integrating Visibility Graph, Simulated Annealing, and A Algorithm - Luo, Guilan; Chen, Zijie; Zeng, Yongwang; Wang, Long; Wen, Shuzhen; Zhang, Mei (2025 2nd International Conference on Algorithms, Software Engineering and Network Security (ASENS), 2025)
This paper presents a multi-task allocation method integrating the visibility graph, A* algorithm, and simulated annealing to enhance scheduling stability and path accuracy in complex environments. The method constructs a path cost matrix and globally optimizes task sequences. Experimental results show a 2% reduction in path length compared to Euclidean-based methods while improving path planning accuracy, allocation efficiency, and stability, providing a robust solution for dynamic multi-task scheduling.